Novel anti-inflammatory mechanism of action of Lyprinol® in the AIA rat model - Halpern, Georges M. (Progress in Nutrition, 2008)
Lyprinol® is the oil of Perna canaliculus, the green-lipped mussel of New Zealand, extracted by liquid CO2 (super-critical extraction); it is free of protein and carbohydrate. A large number of studies have been published on its composition, complex mode of action, activity in animal models, and efficacy in controlling osteoarthritis and moderate asthma in patients; one seminal and critical study was published in this very journal (5). This review article summarizes and presents to the clinicians the results of a comprehensive evaluation of the mechanism of action of Lyprinol in the accepted rat model of AIA. The study was conducted in ABCT (HKPU) under the direction of Samuel CL Lo, PhD. Lyprinol® was shown to: 1. Control pain in the animals; 2. Modulate cytokines with a decrease in cytokines associated with inflammation, and an increase in IL-10; 3. Decrease the synthesis of some proteins associated with inflammation, while increasing the synthesis of MDH. This use of proteomics casts a new light on the anti-inflammatory mechanism of action of Lyprinol®, and differentiates it positively from other omega-3 PUFAs-rich products.